Evaluasi Intent-based Reactive Forwarding dan Reactive Forwarding pada ONOS Controller untuk Pemulihan Kegagalan Jaringan dalam Software Defined Networking - Faris Surya Akbar; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Software Defined Network (SDN) is a current technology developed in computer networks to overcome the drawbacks of traditional networks that are complex and difficult to manage. Although many new functions in SDN have been explored, the issue of resilience to connectivity disruptions in SDN still remains challenging. Measurement studies have revealed that link and node failures are frequent and unexpected in data center and web area network environments. In SDN, there are two approaches in handling link failures, viz: proactive and reactive approaches. In the proactive approach, an alternate path is configured from the beginning, but the possibility of failure of the alternate path earlier than the main path will cause the alternate path to be reconfigured for each failed link, which is not only impractical but also exceeds the limit of entries in the flow table so that the storage required will be even larger. In the reactive approach alternate paths will only be created if there is a link failure, thus reducing the storage load on the switch. ONOS has 2 reactive forwarding methods that can be used in the ONOS controller, namely Intent-based Reactive Forwarding and Reactive Forwarding. Based on the test results, by applying the Intent-based Reactive Forwarding and Reactive Forwarding methods, the average recovery time test results are obtained. The test results show that Reactive Forwarding is still better than Intent-based Reactive Forwarding in the scenario of path termination and alternative path discovery with an average recovery time of 1395.81 ms and 1536.6 ms, respectively.